Bile‐induced peptidoglycan remodelling in Salmonella enterica. (24th June 2014) - Hernández, Sara B.; Cava, Felipe; Pucciarelli, M. Graciela; García‐del Portillo, Francisco; de Pedro, Miguel A.; Casadesús, Josep
Summary Changes in the peptidoglycan (PG) structure of Salmonella enterica are detected in the presence of a sublethal concentration of sodium deoxycholate (DOC): (i) lower proportions of Braun lipoprotein (Lpp)‐bound muropeptides; (ii) reduced levels of muropeptides cross‐linked by L(meso)‐diaminopimelyl‐D(meso)‐diaminopimelic acid (L‐D) peptide bridges (3‐3 cross‐links). Similar structural changes are found in S. enterica cultures adapted to grow in the presence of a lethal concentration of DOC, suggesting that reduced anchoring of Braun protein to PG and low occurrence of 3‐3 cross‐links may increase S. enterica resistance to bile. This view is further supported by additional observations: (i) A triple mutant lacking L, D‐transpeptidases YbiS, ErfK, and YcfS, which does not contain Lpp anchored to PG, is hyper‐resistant to bile; (ii) enhanced 3‐3 cross‐linking upon overexpression of YnhG transpeptidase causes a decrease in bile resistance. These observations suggest that remodelling of the cell wall may be added to the list of adaptive responses that permit survival of S. enterica in the presence of bile.